THE FACTORS OF OUTWARD FDI FROM V4 COUNTRIES FROM THE PERSPECTIVE OF EU AND EMU MEMBERSHIP: A PANEL GRAVITY MODEL APPROACH - Wojciechowski, Liwiusz; Wach, Krzysztof (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The purpose of this article is to explain what factors, from the viewpoint of the Visegrad Group countries, were important determinants in outward FDI. Referring to the eclectic theory of Dunning and the theory of economic development, we decided to answer the question about the determinants for host country choice. We decided to check whether an augmentation of the classical gravity model of international trade allows one to identify push and pull FDI factors. The panel data approach using the Hausman-Taylor estimator was applied in the empirical analysis. The general results allowed us to verify the main hypothesis positively, but some anomalies were observed. In some cases, despite globalisation processes, distance seems to be still a barrier against investment. Decisions concerning the selection of the host country are usually determined by the size of the market measured by GDP per capita, labour productivity. It has been empirically proven that membership in the EMU and the EU, taxation differences and common borders in some cases has a significant influence on the FDI stock concentration. Investment motives among the V4, as well as the size and dynamics of outward FDI have undergone significant changes in the period between 2000–2012.